Unique Case Report of a Meningeal Sarcoma Arising during Ongoing Treatment for Progressing Intraparenchymal Glioma - Richard A. Peterson; Bhavani Kashyap; Pamala A. Pawloski; Anna C. Forsberg; Leah R. Hanson (Case Reports in Oncological Medicine)
Radiation-induced sarcomas in the brain are extremely rare, usually occur with an average latency of 9 years, and are associated with poor outcomes. Latency periods shorter than 1 year may indicate a genetic predisposition such as Li-Fraumeni syndrome. A 34-year-old man underwent initial tumor resection and radiation therapy for a World Health Organization (WHO) Grade II Astrocytoma. Within 6 months, the tumor recurred as WHO Grade III and was treated with temozolomide and then bevacizumab. Despite the patient’s apparent improving condition, MRI revealed new dural-based lesions 10 months after radiation therapy and identified as high-grade sarcoma. The patient resumed bevacizumab, began NovoTTF treatment for progressing glioma, and ifosfamide/doxorubicin for the sarcoma. Genetic testing revealed no pathogenic mutation in the TP53 gene. Ultimately, treatment was unsuccessful and the patient succumbed to glioma and sarcoma within 2 years of initial diagnosis. This case was unique due to the rapidly progressing glioma and sudden appearance of a high-grade sarcoma. It is unusual to have two separate intracranial primary cancers with each requiring a different chemotherapy regimen. We discuss the difficulty of simultaneously treating with separate chemotherapy regimens. It remains unclear whether the sarcoma was induced by the radiation treatment or a genetic predisposition.